2008
DOI: 10.1002/jbm.a.31888
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and endothelial adhesion on fluorosurfactant polymers designed for vascular graft modification

Abstract: A prominent failure mechanism of small-diameter expanded polytetrafluoroethylene (ePTFE) vascular grafts is platelet-mediated thrombosis. We have designed surface modification for ePTFE consisting of a self-assembling fluorosurfactant polymer (FSP) bearing biologically active ligands, including adhesive peptides and polysaccharide moieties. The goal of this biomimetic construct is to improve graft hemocompatibility by promoting rapid surface endothelialization, while minimizing platelet adhesion. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 47 publications
(111 reference statements)
1
63
0
Order By: Relevance
“…[22] The effectiveness of a surfactant polymer coating in preventing protein and platelets adhesion is easily measured under static conditions considered as a ''worst case'' scenario allowing the prolonged undisturbed formation of platelet-surface interactions. [7] The modification with 10% PEG solution incorporates enough hydrophilic chain molecules in the PET nonwoven grafts resulting in a seven-fold decrease platelets adhesion to the level of negative control, i.e. carbon-coated ePTFE (Figure 4), allows to conclude that the surface modification using a 10% PEG solution is sufficient in terms of anti-adhesion platelets effect.…”
Section: Reduction Of Platelet Adhesion On Nonwoven Pet Fiber Structuresmentioning
confidence: 96%
See 1 more Smart Citation
“…[22] The effectiveness of a surfactant polymer coating in preventing protein and platelets adhesion is easily measured under static conditions considered as a ''worst case'' scenario allowing the prolonged undisturbed formation of platelet-surface interactions. [7] The modification with 10% PEG solution incorporates enough hydrophilic chain molecules in the PET nonwoven grafts resulting in a seven-fold decrease platelets adhesion to the level of negative control, i.e. carbon-coated ePTFE (Figure 4), allows to conclude that the surface modification using a 10% PEG solution is sufficient in terms of anti-adhesion platelets effect.…”
Section: Reduction Of Platelet Adhesion On Nonwoven Pet Fiber Structuresmentioning
confidence: 96%
“…To reduce platelet adhesion, coatings of the internal synthetic surface have included grafting polysaccharides or hydrophilic polymers to suppress platelet and protein adhesion on the luminal side, thereby increasing the graft hemocompatibility. [5][6][7][8][9][10] Previously, we developed melt-blown nonwoven PET porous fiber structures, with controllable fiber diameter and pore size allowing an optimized fiber density, size, and inter-fiber pore size for growth and attachment of vascular cells. [2,11,12] The nonwoven PET fiber structures with optimized porosity allow faster endothelialization with higher cellular confluence than commercially available polytetrafluoroethylene (PTFE) and knitted Dacron.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SUV max , MTV does not rely solely on a single point, but rather provides a quantification of metabolic tumor burden. Indeed, we previously demonstrated that increased MTV was associated with higher rates of disease progression and death (6). While our original study demonstrated promise for MTV as a risk-stratifying biomarker, the retrospective study design limits its generalizability.…”
Section: Introductionmentioning
confidence: 92%
“…Our original analysis included 85 patients that we reported on previously (6). The validation dataset in this study consisted of 83 new patients who were accrued after the original dataset.…”
Section: Patientsmentioning
confidence: 99%
“…Fibrin has been proposed as a coating: results have been either discouraging (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) or encouraging as regards anti-adhesive action in platelets and perlecan (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996); one article reported an elastin-like recombining protein [84,85,88]. Single peptides like RGD, cyclic RGD (Mooney DJ et al 1996;Kim BS et al 1998;Wake MC et al 1996) have also been proposed, but only in vitro studies are available (Walpoth BH et al 2007;Lord MS et al 2009;Jordan SW et al 2007;Tang C et al 2009;Larsen CC et al 2007).…”
Section: Permanent Materialsmentioning
confidence: 99%